FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI Studi Kasus di Kecamatan Nogosari, Boyolali, Jawa Tengah - MAHANANTO - -; Salyo - Sutrisno; Candra - F Ananda (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT The objective of this research were to analyze factors influencing the increase of rice production and to analyze the optimum use of production factors on the rice farming. This research was held in October 1999 on 120 farmer in 4 villages of Nogosari-Subdistrict, Boyolali-Regency, Central Java-Province. The data collecting method was divided to in two stages. First, to determine the village sampling done by using a stritified random sampling method and second, to determine the farmers done by a simple random sampling method. The method of collecting data was done an interview using quesionaire instrument. The results of this research were: The used simultaneously model showed that the factors such as the cultivated land width, the quantityof effective labours, the quantity of fertilizers, the quantity of pesticides, the farming experiences, the distance between the farmer houses and the cultivated lands, and the irrigation system had a real influence to the increase of the rice production. The model used in this research had indicated that partially the cultivated land width, the quantity of effective labours, the quantity of fertilazers, the quantity of pesticides, the distence between the farmers houses and the cultivated lands, and the irrigation system had given influences to the increas of rice production, while the farming experiences did not influence to (non-significant) the increasing of rice production. The results of the analyze on the optimum use of production factors had indicated: the cultivated land width was not optimum so that its use should be increased, the quantity of effective labours was not optimum either so that its use should be decreased primarily on the first planting seasion (MT. I) and the second planting seasion (MT. III), while on the third planting seasion (MT. III) it was optimum. Further more, the quantity of fertilizers was not optimum so that its use needed to be decreased and the quantity of pesticides was not optimum either so that its use needed to be increased. Â  Keywords: Rice production, production factor ABSTRAK Tujuan penelitian antara lain untuk menganalisis faktor-faktor yang mempengaruhi peningkatan produksi padi sawah, dan menganalisis tingkat optimasi penggunaan faktor-faktor produksi pada usahatani padi sawah. Penelitian dilakukan terhadap 120 petani sampel di empat desa sampel di wilayah Kecamatan Nogosari, Kabupaten Boyolali, Jawa Tengah. Penarikan sampel dilakukan dalam dua tahap, yang pertama menentukan sampel desa yang dilakukan dengan metode stratified random sampling dan yang kedua menentukan petani sampel yang dilakukan dengan metode simpel random sampling. Pengumpulan data dilakukan dengan teknik wawancara dengan menggunakan instrumen kuesioner. Alat analisis yang digunakan adalah model Fungsi produksi Transendental. Hasil penelitian menunjukkan bahwa: model yang digunaka secara simultan faktor-faktor luas lahan garapan, jumlah tenaga kerja efektif, jumlah pupuk, jumlah pestisida, pengalaman petani dalam berusahatani, jarak rumah petani dengan lahan garapan, dan sistem irigasi berpengaruh sangat nyata terhadap peningkatan produksi padi sawah. Selain itu model yang digunakan menunjukkan bahwa: secara parsial luas lahan garapan, jumlah tenaga kerja efektif, jumlah pupuk, jumlah pestisida (obat-obatan), jarak lahan garapan dengan rumah petani, dan sistem irigasi berpengaruh terhadap peningkatan produksi padi sawah, sedangkan, pengalaman petani tidak berpengaruh (non significant) terhadap peningkatan produksi padi sawah. Sedangkan hasil analisis optimasi (efisiensi ekonomis) penggunaan faktor produksi menunjukkan bahwa: luas lahan garapan belum optimum (efisien) sehingga penggunaannya perlu ditambah, jumlah tenaga kerja efektif tidak optimum sehingga penggunaannya perlu dikurangi terutama pada MT. I dan MT. II sedangkan pada MT. III sudah optimum (efisien), jumlah pupuk tidak optimum sehingga penggunaannya perlu dikurangi, jumlah pestisida (obat-obatan) belum optimum sehingga penggunaannya perlu ditambah. Kata kunci: Produksi padi, faktor produksi.